Why is Semantic Change Asymmetric? The Role of Concreteness and Word Frequency and Metaphor and Metonymy. (2nd January 2022) - Winter, Bodo; Srinivasan, Mahesh
ABSTRACT: Metaphors and other tropes are commonly thought to reflect asymmetries in concreteness, with concrete sources being used to talk about relatively more abstract targets. Similarly, originating senses in diachronic semantic change have often been argued to be more concrete than extended senses. In this paper, we use a dataset of cross-linguistically attested semantic changes to empirically test the idea that asymmetries in figurative language are predicted by asymmetries in concreteness. We find only weak evidence for the role of concreteness and argue that concreteness is not a helpful notion when it comes to describing changes where both originating and extended senses are highly concrete (e.g., skin > bark, liver > lungs). Moreover, we find that word frequency data from English and other languages is a stronger predictor of these typologically common semantic changes. We discuss the implications of our findings for metaphor theory and theories of semantic change.